Решение задачи оптимального секционирования воздушных распределительных сетей в условиях нормирования показателей надежности - Жаркин, А.Ф.; Попов, В.А.; Ткаченко, В.В. (Технічна електродинаміка, 2013)
Рассмотрен новый подход к решению вопросов оптимального секционирования распределительных сетей как одного из эффективных мероприятий по повышению надежности электроснабжения. Предложенный для этой цели эвристический алгоритм позволяет эффективно решить задачу дискретной оптимизации выбора и размещения широкого спектра коммутационных и защитных аппаратов, опираясь на утвержденные НКРЭ нормативные показатели надежности. Запропоновано новий підхід до вирішення питань оптимального секціонування розподільних мереж як одного з ефективних заходів щодо підвищення надійності електропостачання. Використаний для цієї мети евристичний алгоритм дозволяє ефективно вирішити задачу дискретної оптимізації вибору і розміщення широкого спектру комутаційних і захисних апаратів, спираючись на затверджені НКРЕ нормативні показники надійності. The protective devices and switches play an important role in the reliability of electrical distribution systems as they allow to minimize negative effects of electricity interruptions. So the distribution networks optimal sectionalizing traditionally regarded as one of the most common and effective measures to improve the reliability of electric power supply. The approaches to a quantitative estimation and optimization of distribution networks reliability are proposed and discussed in this paper. The developed algorithms allow one to calculate the expected value of reliability indexes both for any load node and for electric power line as a whole. The new approach to the distribution networks optimal sectionalizing is considered in this paper too. Proposed for this purpose, a heuristic algorithm allows one to solve effectively the problem of discrete optimization associated with the selection and location of a wide range of switching and protection devices, using the reliability indices approved by NERC.